2000
DOI: 10.1007/s004390051045
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of mutations in erythrokeratodermias - novel and de novo mutations in GJB3

Abstract: Intercellular channels in skin are a complex and functionally diverse system formed by at least eight connexins (Cx). Our recent molecular studies implicating Cx defects in inherited skin disorders emphasize the critical role of this signaling pathway in epidermal differentiation. Erythrokeratodermia variabilis (EKV) is an autosomal dominant genodermatosis with a striking phenotype characterized by the independent occurrence of transient localized erythema and hyperkeratosis. The disease maps to 1p34-p35, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 38 publications
0
55
0
1
Order By: Relevance
“…To date fourteen human connexin genes have been described, several of which have been associated with human disorders. Four genes causing deafness (GJB1 (Cx32), GJB2 (Cx26), GJB3 (Cx31) and GJB6 (Cx30)) encode connexin proteins (http://www.iro.es/deafness) and distinct dominant mutations in three of these genes (GJB3, GJB2 and GJB6) are involved in skin diseases (reviewed in Kelsell et al, 2001 andRichard et al, 2000). Recently a mutation (F137L) in GJB4 (MIM# 605425) has been identified in affected members of a family with erythrokeratodermia variabilis (EKV; MIM#1 33200) (Macari et al, 2000) but the role of GJB4 in skin disorders has to be confirmed with the identification of additional EKV families with GJB4 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…To date fourteen human connexin genes have been described, several of which have been associated with human disorders. Four genes causing deafness (GJB1 (Cx32), GJB2 (Cx26), GJB3 (Cx31) and GJB6 (Cx30)) encode connexin proteins (http://www.iro.es/deafness) and distinct dominant mutations in three of these genes (GJB3, GJB2 and GJB6) are involved in skin diseases (reviewed in Kelsell et al, 2001 andRichard et al, 2000). Recently a mutation (F137L) in GJB4 (MIM# 605425) has been identified in affected members of a family with erythrokeratodermia variabilis (EKV; MIM#1 33200) (Macari et al, 2000) but the role of GJB4 in skin disorders has to be confirmed with the identification of additional EKV families with GJB4 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Connexin 31 (Cx31) is one of several connexins associated with human disease (see Supporting Text, which is published as supporting information on the PNAS web site, for further details and references). Cx31 is expressed in skin (1,2), and mutations in the human gene (GJB3) are associated with the genetic skin disorder erythrokeratodermia variabilis (3,4). Cx31 is also expressed in the mouse cochlea (5,6) and in peripheral auditory nerves (7), which may explain the association of some mutations in Cx31 with deafness (8).…”
mentioning
confidence: 99%
“…Similarly, studies of human Cx31 (hCx31) suggest that mutations in this connexin may also lead to alterations in trafficking or channel function (26)(27)(28), and some mutations increase cell death when expressed in HeLa, NIH 3T3, or NEB1 cells (26,29). Although mutations in the gene for hCx31 have been associated with autosomal recessive deafness (30) or skin disease (31), most pathogenic hCx31 mutations lead to dominantly inherited disease (3,4,30) and are likely to be caused by either toxic gain-of-function or dominant-negative interactions.…”
mentioning
confidence: 99%
“…Mutations in the Cx gene GJB3 encoding Cx31 were identified in the autosomal dominant skin disorder erythrokeratodermia variabilis (EKV, OMIM 133200) (23), and simultaneously molecular defects in GJB2 (Cx26) were linked to palmoplantar keratoderma associated with congenital hearing loss (OMIM 148350) (18). Subsequent mutation reports of GJB3 in EKV (24,25) and the identification of a common GJB2 mutation (D66H) that underlies mutilating keratoderma with sensorineural deafness (Vohwinkel syndrome, OMIM 124500) (26) tighten this link and provide convincing evidence that gap junctional intercellular communication (GJIC) mediated by Cx signaling is crucial for normal function and differentiation of human skin. These observations then raise the questions: What are connexins and what is their role in skin?…”
mentioning
confidence: 99%
“…In subsequent studies, GJB3 was screened for disease-causing mutations in 7 additional families with EKV and 6 families with PSEK (Table 4, Fig. 2) (24). While no molecular changes were found in PSEK, they identified 4 novel heterozygous se- quence aberrations in EKV.…”
mentioning
confidence: 99%